A review study of rare Earth, Cobalt, Lithium, and Manganese in Coal-based sources and process development for their recovery. (November 2022) - Talan, Deniz; Huang, Qingqing
Highlights: Comprehensive review of REEs, Li, Co, and Mn in coal-based sources was conducted. Critical element contents in various geographic locations were compiled. Separation process for REEs, Li, Co and Mn from coal-based feedstock were reviewed. A conceptual process flowsheet was developed to recover multi-critical elements. Abstract: The world's majority predominantly relies on foreign sources for supplying critical minerals. This renders the countries susceptible to supply chain disruption and urges them to develop alternative sources to compete in technological advancements. Among many proven newly identified sources, coal and coal-based materials present their opportunities. Due to the complex structure of coal, many mineral forms can be found in coal-related sources, including critical element-containing minerals. Among the fifty critical elements and minerals defined by the USGS, the rare earth elements, cobalt, lithium, and manganese, are particularly significant as they have enormous importance in high-technology product development. These critical metals can be found in high concentrations in coal-derived sources, such as coal refuse, coal combustion products, and coal acid mine drainage, and be recovered through various separation techniques. This study aims to advance the understanding of these elements' extraction and commercial potential from coal and coal-related sources and help address the world's challenges in the critical mineral supply chain. The concentrations and occurrences of these four commodities in coal-related sources were first reviewed. Later, their recovery processes were discussed, and a conceptual process flowsheet was proposed to selectively recover the rare earth elements, lithium, cobalt, and manganese from coal-based sources.